ANALISIS STRUKTUR BATIN DALAM PUISI “KERENDAHAN HATI” KARYA TAUFIK ISMAIL - Wulan Suci Nurdianti (IKIP Siliwangi, 2020)
AbstractLiterary work is an expression of the feeling of a person's life that is portrayed in beautiful writing. Poetry is a literary work in the form of writing which is the result of a person's thoughts which are expressed in a dense diction and influenced by the imagination of the author. A poem must have a message or advice and an inner structure implied in it. In this study, researchers will find out about the inner structure contained in a poem. The poem chosen in this research is“Kerendahan Hati” by Taufik Ismail. The researcher considers that the poem implies a meaningful value of life. Therefore, the research aims to find out the inner structure contained in the poem “Kerendahan Hati” by Taufik Ismail. The method chosen by the researcher was descriptive because it was able to describe the phenomema factually and in detail. The results of the analysis carried out show that the poem of